Anti-inflammatory activities of phycoerythrin and phycocyanin on human fibroblast cells - Bahareh Nowruzi; Maryam Zakerfirouzabad (Elsevier, 2024)
Background and Aim: Cyanobacteria are highly regarded for their nutritional value and the scientific community has shown great interest in studying their biological activity and bioactive compounds, especially pigments. They have a wide range of properties, making them potentially useful in various health applications, including dermatology. Given the growing demand for natural products and actives in the cosmetics and medical sectors, these microorganisms have emerged as a valuable source. Therefore, this study investigated the bioactivity of phycoerythrin (PE) and phycocyanin (PC) extracted from Nostoc sp. and Spirulina sp. on CCD-966SK cell lines, specifically focusing on apoptosis, necrosis, anti-inflammatory effects, and enzymatic reactions. Methods: The study involved conducting various bioassays on a human skin fibroblast cell line (CCD-966SK) after performing cyanobacterial cell culture, pigment extraction, and fibroblast cell culture. The bioassays included the MTT test, TNF-α and IL-6 release assays, measurement of human collagen I and III, assessment of apoptosis and necrosis, and analysis of enzyme activity for superoxide dismutase (SOD) and glutathione peroxidase (GPx). Results: The cytotoxicity test results indicated that higher concentrations of PE and PC were associated with lower survival rates. The flow cytometry analysis confirmed a significant increase in necrotic cells and a decrease in living cells at high concentrations of both pigments. The largest percentages of collagen I for PC and PE were identified at 125 and 62.5 ppm, whereas the lowest quantities were reported at 1000 ppm for both pigments. PC and PE had the highest collagen II concentrations at 3.91 and 15.63 ppm, respectively. PC and PE had the lowest collagen II levels at 1000 ppm. PE and PC released anti-inflammatory IL-6 and TNF-a cytokines, indicating high inflammation resistance. Superoxide dismutase (SOD) and glutathione peroxidase (GPx) activity and malondialdehyde (MDA) concentrations showed that both pigments were most active at 1000 ppm. Conclusion: In conclusion, both PC and PE pigments exhibited positive effects in enhancing necrotic, anti-inflammatory, and enzymatic activity against the human skin fibroblast cell line.